Fragilidade de idosos e fatores associados em contexto vulnerável: um estudo longitudinal na atenção primária em saúde - Jesus, Isabela Thaís Machado de (2021)
The population aging raises speculation about the needs of care. The frailty has become a growing concern for the monitoring of integral care for the older adult through prevention, promotion and recuperation. To search the frailty and associated factors can to generate evidence to come improve planning in health care services and long-term care plans. The general objective of this study was: To analyze the relationship between health condition, functionality, quality of life, social support and frailty in the older adults evaluated in 2015 and 2018. At the same time, Describe the perception of community health agents in relation to the identification and monitoring of frailty in the older adults. Participated of the survey older adults with aged ≥ 60 years and members of the teams of 3 family health units. This was a study conducted in a municipality in the interior of São Paulo State. All ethical procedures for research with human beings were respected (No. Opinion: 2.424.616/2017). The study is accessible and disseminated through 3 articles, two of them longitudinal and one with qualitative design with members of the health teams. The first study aimed to assess the predictors of becoming frail between non-frail and vulnerable community-dwelling (n=163). During follow-up, 65.8% of vulnerable subjects became frail. Cox regression and multivariate models revealed that being female (HR: 1.82; 95%CI 1.12-2.94; p = 0.006), being vulnerable according to the Edmonton Frail Scale (HR: 1.69; 95%CI 1.05-2.70; p = 0.006) and having moderate concern of falling (HR=1.72, 95%CI 1.01 – 2.91; p = 0.04) were independent predictors of frailty The second study aimed to analyze whether social support predicts mortality among different frailty groups (n=263). Most study subjects (n=96) were non-frail at baseline and scored well on social support (median 97 points). The global mortality rate in 3 years was 11.8%. The Kaplan-Meier method showed that frail individuals (HR=6.23, CI 2.12-18.33) had an increased risk of mortality when compared with individuals from vulnerable groups (HR=2.34, CI 0.70-7.76). The same was observed when we estimated the HR adjusted to other variables. Material social support was independently associated to the mortality rate among frailty groups. The third article aimed to describe the perception of family health team members in relation to the identification and monitoring of frailty in the older adults, considering potentialities and challenges in the scope of primary health care. For data collection were made focus groups were conducted with12 members of family health teams. From the topics proposed for the discussion, the results obtained showed the use of instruments to identify frailty, monitoring through home visits and discussions in team meetings. Our results are observational and it was possible to highlight the predictors of frailty, as well as the predictors for social support and the appearance of mortality in older people in a socially vulnerable context. The qualitative findings showed the use of instruments for the identification and monitoring of frailty through home visits and team discussions.